2008
DOI: 10.1186/1471-2229-8-125
|View full text |Cite
|
Sign up to set email alerts
|

ESKIMO1 is a key gene involved in water economy as well as cold acclimation and salt tolerance

Abstract: Background: Drought is a major social and economic problem resulting in huge yield reduction in the field. Today's challenge is to develop plants with reduced water requirements and stable yields in fluctuating environmental conditions. Arabidopsis thaliana is an excellent model for identifying potential targets for plant breeding. Drought tolerance in the field was successfully conferred to crops by transferring genes from this model species. While involved in a plant genomics programme, which aims to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 78 publications
4
65
0
Order By: Relevance
“…HARDY, an ethylene-responsive transcription factor, is an example of a single gene identified from studies with the model species Arabidopsis that has been demonstrated in rice to confer enhanced drought (and salt) tolerance when a specific mutant allele is overexpressed [51]. ESKIMO1 is another promising example of a major genetic player affecting water economy (as well as cold and salt tolerance), with lack-of-function Arabidopsis mutants show better fitness in drought conditions [52] by altering hydraulic conductivity in the vascular tissues and increasing ABA levels [53]. Natural genetic variation studies in crops [54,55] and model species [56] are also helping to unveil alleles conferring drought tolerance traits, which can be used as powerful tools on breeding programs via either traditional or molecular approaches.…”
Section: Watermentioning
confidence: 99%
“…HARDY, an ethylene-responsive transcription factor, is an example of a single gene identified from studies with the model species Arabidopsis that has been demonstrated in rice to confer enhanced drought (and salt) tolerance when a specific mutant allele is overexpressed [51]. ESKIMO1 is another promising example of a major genetic player affecting water economy (as well as cold and salt tolerance), with lack-of-function Arabidopsis mutants show better fitness in drought conditions [52] by altering hydraulic conductivity in the vascular tissues and increasing ABA levels [53]. Natural genetic variation studies in crops [54,55] and model species [56] are also helping to unveil alleles conferring drought tolerance traits, which can be used as powerful tools on breeding programs via either traditional or molecular approaches.…”
Section: Watermentioning
confidence: 99%
“…Therefore, the authors suggested that the freezing tolerance exhibited by the esk1 mutant was a side effect of a constitutive acclimation to dehydration. Based on transcriptome analysis, a major role of ESK1 in the plant response to water shortage and in the whole-plant water economy was also suggested by Bouchabke-Coussa et al (2008). The improved tolerance to multiple stresses as a consequence of the altered expression, in mutant or transgenic lines, of a gene normally activated in response to a specific stress, depends on the overlap at the molecular level of the response to different stresses.…”
Section: Drought Stress Response In Arabidopsismentioning
confidence: 99%
“…The authors also reported the integrated analysis of drought-induced transcriptome and metabolome changes. The relationship between temperature and drought responses has been widely documented (Yamaguchi-Shinozaki & Shinozaki, 2006); mutations affecting the tolerance to both stresses, as well as transgenic plants with increased tolerance to both stresses, have been described (Bouchabke-Coussa et al, 2008;Kasuga et al, 1999;Mattana et al, 2005a). An emblematic example of the overlap between the temperature and drought stress responses is represented by the eskimo1 (esk1) mutant phenotype.…”
Section: Drought Stress Response In Arabidopsismentioning
confidence: 99%
“…PHENOPSIS has been developed as an automated controlled drought screen, which was used to compare the performance of different Arabidopsis ecotypes (accessions) and resulted in the identification of a resistant accession, An1 . Controlled drought was also used to study the response of the Arabidopsis erecta mutant and ERECTA gene complementation (Masle et al, 2005), the overexpression of the Arabidopsis ESKIMO1 gene (Bouchabke-Coussa et al, 2008), and overexpression of the Pro biosynthesis gene in chickpea (Cicer arietinum;Bhatnagar-Mathur et al, 2009).…”
mentioning
confidence: 99%